Handbook of Evidence-Based Day Treatment Programs for Children and Adolescents - Leffler, Jarrod M.; Frazier, Elisabeth A. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book examines the intermediate level of mental health services with a focus on partial hospitalization program (PHP) and intensive outpatient program (IOP) models of care for youth. It reviews the history of PHPs and IOPs and highlights their current care models, demonstrating the increase in the development and implementation of evidence-based treatment (EBT) practices. The book explores issues relating to program development, implementation, and considerations for sustainability. It provides interventions designed to enhance the well-being of youth who are experiencing a range of mental health concerns as well as strategies to engage and involve their families. In addition, the book offers feasible strategies for measuring outcomes and applying these results to meaningful clinical evaluations in PHP and IOP settings. It describes the process of accessing and using these intermediate services as well as additional treatment resources that may be necessary in the continuum of mental health care for youth. Key areas of coverage include: The history and purpose of mental health care and the role of day treatment programs for youth. Working with program administration and other stakeholders, identifying a patient population, and engaging community and referral sources. The importance of family involvement, coordination of care, and simultaneously addressing the transactional relationship between physical and mental health. Transitioning youth from pediatric mental health services into the adult mental health system. Working with a diverse patient population in intermediate treatment programs. Providing practical information for families and practitioners navigating the pediatric mental health continuum of care. The Handbook of Evidence-Based Day Treatment Programs for Children and Adolescents is a must-have resource for researchers, professors, and graduate students as well as clinicians, therapists, course instructors, and other professionals in child and adolescent psychiatry, clinical child and school psychology, social work, counseling, public health, family studies, developmental psychology, pediatrics, and all related disciplines.
Chapter 1. Introduction and Overview of Day Treatment Programs -- Chapter 2. The History and Purpose of Day Treatment Programs -- Chapter 3. Program Development and Administration in Day Treatment Settings -- Chapter 4. Implementation and Training -- Chapter 5. Assessment and Evaluation of Outcomes in Youth Day Treatment Programs -- Chapter 6. Perspectives on General Partial Hospital Programs for Children -- Chapter 7. Child and Adolescent Integrated Mood Program -- Chapter 8. The UCLA Achievement, Behavior, Cognition (ABC) program -- Chapter 9. Center for Autism and Developmental Disabilities Partial Hospitalization Program -- Chapter 10. Dialectical Behavior Therapy -- Chapter 11. Obsessive Compulsive and Related Disorders -- Chapter 12. Family-Based Interdisciplinary Care for Children & Families with Comorbid Medical & Psychiatric Conditions: The Hasbro Children's Partial Hospital Program -- Chapter 13. Development and Implementation of an Intensive Outpatient Program for Suicidal Youth -- Chapter 14. Seattle Children's Hospital's Obsessive Compulsive Disorder Intensive Outpatient Program -- Chapter 15. Evidenced Based Programming for LGBTQ Young Adults: An Intensive Outpatient Model -- Chapter 16. Adolescent Dialectical Behavior Therapy Intensive Outpatient Programs -- Chapter 17. Co-occurring Disorders -- Chapter 18. Pediatric Pain Programs: a Day Treatment Model at Boston Children's Hospital -- Chapter 19. Transitioning to Adult Services: Young Adult Partial Hospitalization and Intensive Outpatient Programs -- Chapter 20. Integrating Day Treatment in the School Setting -- Chapter 21. Wilderness Therapy -- Chapter 22. Family Engagement and Coaching in 5-Day Intensive Treatment Program for Youth with Anxiety Disorders and OCD -- Chapter 23. Telehealth Adaptations in Day Treatment Programs -- Chapter 24. Inpatient Psychiatric Hospitalization -- Chapter 25. The Youth Crisis Stabilization Unit: An Alternative Psychiatric Treatment Model -- Chapter 26. Strategies to Navigate Day-Treatment Services and Follow-up Plans: a Guide for Families and Providers.
Keywords: Developmental psychology; Social psychiatry; Public health; Developmental Psychology; Child and Adolescence Psychology; Clinical Social Work; Public Health